The Dialectal Phenomena in the XVIII Century Manuscript Dictionaries of Synonyms - HOVHANNISYAN, NAZIK (Bulletin of Yerevan University B: Philology, 2021)
In the manuscript dictionaries, some rows of synonyms end with words, which existed in the Armenian dialects. In this article these words are examined as interferences of the authors of the manuscript dictionaries; they replenished the rows and added some words of their own dialects. The words խզարել “to saw off”, ծիւ ծիւ առնել “to tear to pieces”, տոռնը “rope, cord, thread”, ջաւ (id.), փողպատ “collar”, ծիրանի գօտի “iris, rainbow”, աղեղն ամպոյ (id.) are considered.